Investigating the moderator effect of fear of COVID-19 in the relation between communication anxiety and self-efficacy - Nesrullah Okan (Educational Process: International Journal)
Background/purpose – COVID-19 has forced many people to face psychological problems, with already difficult living conditions having become progressively more challenging. Individuals with low pre-pandemic levels of communication anxiety saw those levels increase, which negatively affected their self-efficacy. Therefore, the main purpose of this study was to examine the moderating effect of fear of COVID-19 on the relationship between communication anxiety and self-efficacy.